Synthesis of 4-Acryloylmorpholine- based Hydrogels and Investigation of their Drug Release Behaviors - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SOC BRASILEIRA QUIMICA, 2013)
In this study, hydrogels based on an amphiphilic, water soluble, bisubstituted and biocompatible acrylamide derivative, namely 4-acryloylmorpholine (4-AcM), were prepared. 4-AcM based hydrogels with different compositions were synthesized by photopolymerization from the mixtures of poly(ethylene glycol) diacrylate (PEG-DA) and poly(2-hydroxy ethyl methacrylate) (HEMA), and characterized by Fourier transform infrared spectroscopy (FTIR). Gel percentage and equilibrium swelling ratios were determined. Images obtained by scanning electron microscopy (SEM) confirmed porous structure of the hydrogels. Ciprofloxacin. HCl was chosen as a model drug in order to understand the drug loading and release behaviors of the hydrogels. As 4-AcM content increased, higher drug release was observed. On the other hand, the increase in crosslinking density due to PEG-DA content resulted in the swelling decrease of the hydrogel and reduced the diffusion of the drug.
Keywords: hydrogel; photopolymerization; drug release; 4-acryloylmorpholine; ciprofloxacin; MICROSPHERES